2016
DOI: 10.4236/ijmpcero.2016.51001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced Bystander Effect: From <i>in Vitro</i> Studies to Clinical Application

Abstract: In the past 20 years, the classic paradigm in radiobiology recognizing DNA as the main target for the action of radiation has changed. The new paradigm assumes that both targeted and non-targeted effects of radiation determine the final outcome of irradiation. Radiotherapy is one of the main modality treatments of neoplastic diseases with intent to cure, or sometimes to palliate only, thus radiation-induced non-targeted effect, commonly referred to as the radiation-induced bystander effect (RIBE) may have a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…The terms commonly refer to distant tumor regression after localized irradiation [97]. Abscopal effects were observed in different tumor types after conventional radiotherapy, as well after stereotactic ablative radiotherapy almost always combined with immunotherapy which act synergistically (reviewed by [13]). The mechanism of this synergy is based on reduction by radiation of immunosuppression and tolerance of tumor by microenvironment of the body, followed by induction of immune response [98,99].…”
Section: Clinical Look At Bystander Effect Induced By Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The terms commonly refer to distant tumor regression after localized irradiation [97]. Abscopal effects were observed in different tumor types after conventional radiotherapy, as well after stereotactic ablative radiotherapy almost always combined with immunotherapy which act synergistically (reviewed by [13]). The mechanism of this synergy is based on reduction by radiation of immunosuppression and tolerance of tumor by microenvironment of the body, followed by induction of immune response [98,99].…”
Section: Clinical Look At Bystander Effect Induced By Radionuclidesmentioning
confidence: 99%
“…RIBE is communicated through cell-to-cell gap junctions or by extracellular environment, and typically refers to the damaging events such as reduced clonogenic survival [5,6], increased sister chromatid exchange [7,8], formation of micronuclei and cell death via apoptosis and necrosis [9][10][11][12], all presented in vitro, although similar events appear also in vivo. Many preclinical studies revealed the appearance of bystander effect and abscopal (out of field effect) in vivo (reviewed by [13]. The abscopal effect is an immune-mediated phenomenon.…”
mentioning
confidence: 99%
“…8,9 IR causes not only targeted effects but also non-targeted effects several cell generations after initial exposure. [1][2][3][4][5][6] Therefore, we asked whether radiation effects somatic cell reprogramming with respect to the two different radiation responses. To assess the effect of targeted radiation on the reprogramming of somatic cells to pluripotency, as shown in Fig.…”
Section: Direct Exposure To Radiation Attenuates Pluripotency Inductimentioning
confidence: 99%
“…These responses can be observed in either cells exposed to signaling molecules released by irradiated cells, which activate non-irradiated cells or in subsequent generations of irradiated cells. 2,3 Among radiation-induced non-targeted response, the delayed effect such as delayed reproductive death and chromosomal instability have been described in the descendants of irradiated cells. Its persistence over many generations after irradiation has been considered relevant for the human health risk associated with radiation-induced carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It disrupts the redox balance, resulting in irreversible changes in the cell, and causing severe disturbances within the entire metabolic pathways (Widel et al, 2014). Such UVinduced oxidative stress and imbalance may lead to diseases such as diabetes, atherosclerosis, or cancer (Valko et al, 2005;Karpińska & Gromadzka, 2013;Kasperczyk et al, 2013;Buttke & Sandstrom, 2016;Widel, 2016).…”
Section: Introductionmentioning
confidence: 99%